2003
DOI: 10.1258/135763303322596246
|View full text |Cite
|
Sign up to set email alerts
|

Low-bandwidth telerehabilitation for patients who have undergone total knee replacement: Preliminary results

Abstract: We have developed a low-bandwidth, Internet-based telerehabilitation system to provide outpatient rehabilitation to patients who have undergone total knee arthroplasty. The preliminary efficacy of this treatment programme in terms of both physical and functional objective outcome measures was assessed on 21 patients. Subjects receiving a six-week rehabilitation programme were randomized to the telerehabilitation system or the usual face-to-face method. The physical and functional improvements in the telerehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 11 publications
(10 reference statements)
1
71
1
Order By: Relevance
“…The randomized trial was a televideo-guided 6-week exercise program for 21 patients recovering from total knee replacement. This study found no significant difference between face-to-face and remote guides [17].…”
Section: Introductioncontrasting
confidence: 69%
“…The randomized trial was a televideo-guided 6-week exercise program for 21 patients recovering from total knee replacement. This study found no significant difference between face-to-face and remote guides [17].…”
Section: Introductioncontrasting
confidence: 69%
“…The eHAB telerehabilitation system enables videoconferencing at 320 × 240 pixel resolution and real-scale measurement of the patient's performance on assessment items (such as balance, joint range of motion, muscle strength, and gait) through a suite of optical calibrated assessment tools. This system has been described elsewhere in the literatures [11,[13][14][15][16][17]21]. The systems were connected via a 3G network connection (Telstra Next G; Melbourne, Australia) with theoretical downlink speeds of 7.2 Mbps and uplink speeds of 5.7 Mbps.…”
Section: Telerehabilitation Assessmentsmentioning
confidence: 99%
“…A research team at the University of Queensland, Australia, has developed a computer-based videoconferencing system call eHAB that combines highquality videoconferencing with a battery of measurement tools that can objectively measure various aspects of functional performance across an Internet link. Studies demonstrating the validity and reliability of this system have been performed to examine physical outcome measurements [6,10], observational kinematic gait analysis [11], upper-limb range of motion in stroke patients [12], lowerlimb range of motion in an orthopedic population [13], the effectiveness of rehabilitation following total knee replacement surgery [14][15][16], and diagnostic accuracy of ankle injuries [17]. Other studies using similar videoconferencing equipment have demonstrated that telerehabilitation assessments of Functional Reach, the European Stroke Scale, and the Functioning Everyday with a Wheelchair-Capacity can be performed accurately compared with face-to-face encounters [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Tele-rehabilitation appears to be an effective method by which to deliver therapy, and many studies demonstrate positive outcomes in terms of improving physical functioning (Burdea, Popescu, Hentz, & Colbert, 2000;Lai, Woo, Hui, & Chan, 2004;Piron et al, 2004;Reinkensmeyer, Member IEEE, Pang, Nessler, & Painter, 2002;Russell, Buttrum, Wootton, & Jull, 2003Sveistrup et al, 2003); with no significant differences found between face-to-face and tele-rehabilitation interventions (Guilfoyle et al, 2003;Russell et al, 2003Russell et al, , 2004Sveistrup et al, 2003). As with telemedicine interventions in general, tele-rehabilitation was well received by both patients and caregivers (Lai et al, 2004;Reinkensmeyer et al, 2002;Russell et al, 2003Russell et al, , 2004Sveistrup et al, 2003), and was easy to use even among patients with low computer literacy (Russell et al, 2003(Russell et al, , 2004.…”
Section: Videoconference-based Physiotherapy and Tele-assessment Formentioning
confidence: 99%
“…As with telemedicine interventions in general, tele-rehabilitation was well received by both patients and caregivers (Lai et al, 2004;Reinkensmeyer et al, 2002;Russell et al, 2003Russell et al, , 2004Sveistrup et al, 2003), and was easy to use even among patients with low computer literacy (Russell et al, 2003(Russell et al, , 2004.…”
Section: Videoconference-based Physiotherapy and Tele-assessment Formentioning
confidence: 99%